India, China and Globalization The Emerging Superpowers and the Future of Economic Development - Mahtaney, P. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
The momentum of economic progress in India and China will bring about the next major shift in geopolitics. This book analyzes the economic experience of both countries in the context of development and globalization, and offers insights that could be crucial for development thinking.